The Effect of Dietary Propylene Glycol on the Fatty Acid Composition of Three Fat Depots in Male Akkaraman Lambs - Cafer Tayyar Ateş; Ufuk Kaya; İrem Karaaslan; Hüseyin Özkan; Akın Yakan (Veterinary Medicine and Science)
ABSTRACT This study tested the effects of propylene glycol (PG) on the fatty acid composition of Akkaraman lambs in three different anatomical depot locations (ADLs). Twenty‐four lambs were assigned to a randomized complete block design comprising three groups of 8 animals as follows: Con, 1.5%, body weight (BW)0.75 (PG1.5) and 3% BW0.75 supplemental PG. The animals were slaughtered 90 days after the commencement of feeding. Tail, perirenal and back fat were collected, and their fatty acid compositions were analysed. PG was associated with lower levels of capric acid (C10:0) and lauric acid (C12:0), and higher levels of arachidic acid (C20:0), D‐ɣ‐linolenic acid (C20:3n6), behenic acid (C22:0), docosadienoic acid (C22:2n6), tyricosylic acid (C23:0) and eicosapentaenoic acid (C20:5n3; p < 0.05, p < 0.01 and p < 0.001). The ADLs differed for all fatty acids except C12:0 and C14:0 (myristic acid). Perirenal fat had the highest SFA levels, while n6/n3 was higher in tail fat than in fat from the other ADLs (p < 0.001). The high correlation of ∆9 C16 and ∆9 C18 index values with other sum and index values indicates that desaturation enzyme activity was elevated in the lambs’ depot fats (p < 0.05, p < 0.01 and p < 0.001). This suggests that perirenal fats have less favourable fatty acid compositions than the other ADLs.